UPTAKE OF DIFFERENT DYES BY TWO NEW STRAINS OF MICROALGAL DRY BIOMASS - Abdulkareem, P. ` M.; Anwer, S. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The control of wastewater pollution has become of increasing importance in recent years. The release of dyes into the environment constitutes only a small proportion of water pollution, but dyes are visible in small quantities due to their brilliance. In this study Spirulina subsalsa and Scenedesmus ecornis microalgae isolated from Chnarok and Taq-Taq Koya city and  its ability to uptake different dyes. Batch studies were conducted at separate biosorbent doses ,dye concentration, pH, temperature and agitation speed. Optimum adsorption of dyes by Spirulina subsalsa and Scenedesmus ecornis showed in reactive yellow (89.3%, 90.4%) respectively at 50 mg l-1, 30℃, pH 8, 150 rpm, dosage 1.2 g ml-1.